Decision making for net zero policy design and climate action: considerations for improving translation at the research-policy interface: a UK Carbon Dioxide Removal case study - Workman, Mark; Heap, Richard; Mackie, Erik; Connon, Irena (Frontiers in Climate, 2023)
The impacts of climate change on society and the natural environment are being experienced now, with extreme weather events increasing in frequency and severity across the globe. To keep the Paris Agreement's ambition of limiting warming to 1.5ºC above pre-industrial levels there is now also a need to establish and scale a new sector to remove CO2 at Giga-tonne scale for over a century. Despite this mounting evidence and warnings, current climate policy in the UK and globally falls far short of achieving the required reductions in CO2 emissions or establishment of a new removal sector needed to stave off the risks posed by climate change. Some of the science on climate risk is abundantwell evidenced, but the policy response is lacking in effectiveness. Other evidence to design policy, such as Carbon Dioxide Removal (CDR), is fraught with deep uncertainty.Why are the plethora of scientific evidence, assessments and decision support tools available to decision and policymakers not always translating into effective climate-net zero policy action? How can emergent evidence be brought in introduced to shape new sectors such as CDR? What are the capacity gaps? Through a combination of literature review, interviews and UK policy workshops over 17 months these are some of the questions that this contribution sought insight.We set out three recommendations for policymakers and other stakeholders, including academic researchers and third sector organisations, to address the identified gaps associated with translating climate risk and net zero decision support into effective climate policy:Enhance collaboration between decision-makers, policymakers, analysts, researchers, and other stakeholders to co-develop and co-design operational climate risk assessments and policies, relevant to context.Identify the research and capacity gaps around climate risk decision-making under uncertainty, and work with stakeholders across the decision value chain to ensure those gaps are addressed.Co-create effective translation mechanisms to embed decision-support tools into policy better, employing a participatory approach to ensure inclusion of diverse values and viewpoints.It is fundamental that there is improvement in our understanding about how we can make good decisions and operationalise them, rather than simply focus on further research on the climate risk and net zero problem.